Penerepan Budaya Inovasi & Kreatifitas dengan Metode DMAIC dan Kaizen ( Continuous Improvement) pada PT. Indolakto Pasuruan - Yasman Yasman; Limgiani Limgiani (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2024)
A culture of innovation is very important to implement in a company to be able to maintain the existence and survival of the company. Successful innovation depends significantly on ability, skills and interpreting a rapidly changing environment. Apart from that, employee involvement also influences success in innovation. Innovation and creativity use the DMAIC (Define, Measure, Analyze, Improve and Control) method which is associated with KAIZEN in Japanese terms, which means "continuous improvement" which emphasizes human effort, morals, communication, training, cooperation, empowerment and self-discipline . The purpose of this research is to find out the strategy carried out by PT. Indolakto Pasuruan in motivating its employees to implement a culture of innovation as well as identifying factors inhibiting its implementation and efforts made to minimize these obstacles. This research uses qualitative research methods and tests the validity of this research data using source triangulation and member checking. From the results of this research, researchers concluded that implementing a culture of innovation in companies can have a positive impact on the company's survival. Research implications - This research makes a contribution to human resource management related to corporate culture.